Chemical constituents and biological activities of essential oils and extractivities from Agathis borneensis - Fouziah, Alet (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The chemical constituents of essential oils and extractives from resin, bark and heartwood of Agathis borneensis were studied using gas chromatography-flame ionization detector (GC-FID) and gas chromatography-mass spectrometer (GC-MS). The essential oils were extracted using hydrodistillation method while the extractives were extracted using solvent with increasing polarity; hexane, dichloromethane, ethyl acetate and methanol. The major components in the resin oil were a-pinene (31.15 %), 8- limonene (17.92 %), B-pinene (11.36 %) and terpinen-4-ol (8.41 %). While, B-pinene (9.14